Development and use of a new medium to detect yeasts of the genera Dekkera/Brettanomyces - Malfeito-Ferreira, Manuel (2009)
Aims: The objectives of this work were to develop a selective and/or differential medium able to effciently recover Dekkera/Brettanomyces sp. from wine-related environments and to determine the relationship between these yeasts and the 4-ethylphenol content in a wide range of wines. Methods and Results: The selectivity of the developed medium was provided by the addition of ethanol, as single carbon source, and cycloheximide. The inclusion of bromocresol green evidenced acid-producing strains. The inclusion of p-coumaric acid, substrate for the production of 4-ethylphenol, enabled the differentiation by smell of Dekkera/Brettanomyces sp. from all other yeast species growing in the medium. The medium was used either by plating after membrane filtration or by the Most Probable Number (MPN) technique. In 29 white and 88 red randomly collected wines, these yeasts were found only in red wines at levels up to 2500 MPN ml±1, but constituted less than 1% of the total microbial flora. In red wines, 84% showed detectable amounts of 4-ethylphenol up to 4430 lg l±1 while 28% of the white wines showed detectable levels up to 403 lg l±1. Conclusions: The use of the medium proposed in this work evidenced the presence of low relative populations of Dekkera/Brettanomyces sp. even in wines contaminated by fast-growing yeasts and moulds. Significance and Impact of the Study: Further ecological studies on Dekkera/Brettanomyces sp. should take into account the use of highly specific culture media in order to establish their true occurrence in nature